Comparative Growth Analysis and Yield Performance of Glycine Max under Jatropha Curcas Based Agrisilviculture System of Agroforestry in the Northern Part of Bangladesh - Das, Niamjit (Journal of Forests, 2015)
This research was conducted at the Agroforestry Research Farm, Hajee Mohammad Danesh Science and Technology University to quantify the effects of pruning height in Jatropha curcas L. (Jatropha) and fertility levels of the recommended dose of NPK in Glycine max L. (Soybean) on crop growth parameters and yield in the agri-silviculture system of Agroforestry. The pruning in Jatropha and fertility level favored growth parameters with varying magnitudes. Six growth indices CGR, RGR, NAR, LAI, RLGR, and SLW were observed to be higher under various pruning heights and reduced under no pruning. After that, the scale of yield varied with pruning heights and fertility levels. Grain, straw, and biological yield of 100 cm pruning height in Jatropha increased by 15.38 %, 13.74 %, and 14.61 % respectively compared to sole crop and other pruning height levels. At that time, it showed that these three yields of 100 % of the recommended dose of NPK (100 % RDF) in Soybeans are comparatively higher than other fertility levels. Hence, a proper pruning system and optimum fertility level are important for improving Soybean yield under the agri-silviculture system. It ensures higher income to the farmers and efficient land management compared to its sole cropping.